Baltų kalbų paleokomparatyvizmo (XVI a.) hebrajiškoji samprata ir jų mįslingas tekstelis - Dini, Pietro U. (Baltistica, 2005)
A HEBREW THEORY CONCERNING THE BALTIC LANGUAGES IN THE CONTEXT OF 16TH C. PALAEOCOMPARATIVISM AND A RELATED ENIGMATIC TEXT In the wider context of the history of the linguistic ideas concerning the Baltic languages, and especially of the Palaeocomparativism of the 16th century, we should also like to present and comment on the idea that the Baltic languages derive from the Hebrew language (this theory completes the picture I already tried to give in a series of papers on the Slavic, Roman, Fourfold, Greek and other linguistic theories). The main authors and works related to this idea in the 16th c. are: Johannes Funck (1518-1566) and his Chronologia ab orbe condito (Nürinberg, 1545; Königsberg, 1552, 1566; Wittenberg 1578); Severin Göbel (1530-1612) and his works: De Succino Libri Duo (1565), Einfeitiger Jedoch gründtlicher Bericht vnd Bedencken, Vom vrsprung des Agadt oder Bernsteins... (1616); Johannes Loewenklau (1537-1593) and his works Annales Sultanorum Othmanidarum (Frankfurt am Main, 1588), Neuwe Chronica Tiirckischer nation (Frankfurt am Main, 1590). Loewenklau (1588) quotes the enigmatic text Ieru Ieru Masco Lon, which was repeated with some variants in later editions and by other authors of that time. The text has resisted until now many attempts at an explanation (M. Praetorius, Ph. Ruhig, X. Bohusz). Previous explanations of the text are discussed in this paper and a new interpretation is proposed. Finally we consider the text to belong to the Lith. tradition and we explain it as follows: “Lord, Lord (cf. Lith. exclamation jerau! < germ. Herr) throw (cf. Lith. mesk) beer (cf. Lith. alų, i.e. alaus statinę, or sim.)”. Linguistic and cultural arguments supporting this explanation are also given.